Performance Comparison of Coagulation and Adsorption for Gambier Wastewater Treatment Using Poly Aluminium Chloride (PAC), Calcium Hypochlorite, and Activated Carbon - Dr. Eng. Erda Rahmilaila Desfitri; Setiaman Bawamenewi; Wahyudiansyah Kurinci; Edwina Zainal; Nofri Naldi; Reni Desmiarti (Universitas Nusa Bangsa, 2025)
Industrial wastewater from gambier (Uncaria gambir Roxb.) extraction is characterized by high organic loads, intense coloration, and elevated levels of total dissolved solids (TDS), which often exceed regulatory discharge limits. This study evaluated the performance of two chemical coagulants, Poly Aluminium Chloride (PAC) and calcium hypochlorite (Ca(OCl)₂), and one physical adsorbent, coal-based activated carbon (CW 130 AR), in treating gambier wastewater. The experimental work assessed their effects on chemical oxygen demand (COD), TDS, and color, alongside adsorption equilibrium modeling using Langmuir and Freundlich isotherms. Results demonstrated that PAC achieved 89% COD removal, and calcium hypochlorite reached 82%. However, both coagulants were ineffective at reducing Total Dissolved Solids (TDS) and occasionally increased dissolved solids due to residual ionic species. In contrast, activated carbon achieved COD and color removal efficiencies exceeding 95%, though it provided only modest TDS removal (≈85%). Adsorption isotherm analysis confirmed that COD removal by activated carbon followed the Langmuir model (R² = 0.9488), indicating monolayer chemisorption on a homogeneous surface. Meanwhile, PAC and calcium hypochlorite showed weak conformity to Langmuir and Freundlich models, confirming coagulation/flocculation as their dominant removal mechanism. This study provides the first comparative performance evaluation of coagulation and adsorption processes for gambier industry wastewater, demonstrating that a hybrid or sequential treatment strategy can achieve more comprehensive pollutant removal. By enhancing treatment efficiency, reducing industrial effluent discharge, and enabling potential water reuse, this work supports Sustainable Development Goals (SDGs) 6 (Clean Water and Sanitation) and 12 (Responsible Consumption and Production).